Physiotherapy Management for Patients with Dextra Knee Osteoarthritis at RSJ Prof. Hospital. Dr. Soerojo Magelang - Munzirin, Reni Mardika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Background: Osteoarthritis Knee Dextra is a degenerative joint disease in the form of damage to joint cartilage that develops slowly, the cause is unknown and the joint disease is more common than other joint diseases. Objective: To determine the implementation of Physiotherapy in reducing pain, increasing joint range of motion and increasing muscle strength in cases of Dextra Knee Osteoarthritis using Infra-Red (IR) Transcutaneous Electrical Nerve Stimulation (TENS) and exercise therapy (TL) modalities. Results: After undergoing therapy 6 times, pain assessment results were obtained for T1 silent pain: 1 becomes T6 : 1, tenderness T1 : 4 becomes T6 : 2, movement pain T1 : 4 becomes T6 : 3, increased joint range of motion S: T1 : S 0 – 0 – 125 becomes T6 : S 0 – 0 – 135 , increase in right knee muscle strength, hip flexor T1: 4- to T6: 4+, hip extensor T1: 4- becomes T6 : 4+. Conclusion: Infra-Red (IR) can reduce pain in the right knee in cases of Osteoarthritis Knee Dextra, exercise therapy Transcutaneous Electrical Nerve Stimulation (TENS) can reduce pain in the right knee in cases of Osteoarthritis Knee Dextra (TL), can increase the range of motion of the right knee joint in cases of Osteoarthritis Knee Dextra and can increase muscle strength in cases of Osteoarthritis Knee Dextra.